Conflict and communication : a guide through the labyrinth of conflict management - Shapiro, Daniel, 1971- (International Debate Education Association, 2004)
Annotation "Conflict and Communication offers educators a practical curriculum on conflict management that helps students understand the nature of conflict and learn the skills that will enable them to deal with conflicts in their lives. The book is divided into two parts: Conflict Management and Student Mediation." "Conflict Management contains 60 hands-on activities that help students understand how personal values are formed, how misperceptions and misunderstandings arise and affect relationships, and how they can communicate effectively. The activities explain the roots and consequences of conflict, offer specific strategies for dealing with conflict, and help students discover basic human rights and their connection to conflict."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved